Information About Zoonotic Disease Risks Reduces Desire to Own Exotic Pets Among Global Consumers - Moorhouse, Tom P.; D'Cruze, Neil C.; Macdonald, David W. (Frontiers in Ecology and Evolution, 2021)
Demand for exotic pets is a substantial driver of the illegal wildlife trade. Previous work has suggested that this demand could be reduced by conservation marketing messaging highlighting the potential consequences to individual purchasers, in the form of zoonotic disease risks, or legal ramifications. Such work, however, has been limited only to respondents from culturally Western countries, and has not accounted for how underlying attitudes to the keeping of exotic pets may influence desire to own one, or affect the effectiveness of demand reduction messaging. We surveyed 1,000 respondents in each of Brazil, China, USA and Vietnam, showing each five mammal, bird, and reptile pets in random order. Each pet was accompanied with either a “control” statement, describing the species' diet, or one of four types of “treatment” statement describing zoonotic disease, animal welfare, legal or species conservation consequences. Respondents were asked to rate how much they would like to own the pet on a 1–10 scale. All respondents demonstrated decreased desire to own a given exotic when shown any of the types of treatment information, but disease information provoked the greatest decrease, relative to controls (a mean decrease of 26.9%, compared with 16.2, 17.9, and 18.9% for legality, welfare and conservation information, respectively). We also found that respondents with the highest stated likelihood of purchasing pets possessed a series of beliefs that could facilitate this purchase while maintaining an ethical self-image: in particular they believed that shops were well-regulated, and that they were able to distinguish captively-bred from wild caught animals. In summary all respondents of any nationality were motivated particularly to avoid the risk of zoonotic disease, and we recommend that demand reduction campaigns leverage this desire, particularly in the new context of COVID-19.